The Effect Of Corporate Real Estate Strategic Practices On Performance Of Five-Star Hotels In Sri Lanka - Kaluthanthri, Prathap Chandima (2020)
Corporate Real Estate (CRE) and Corporate Real Estate Strategy (CRES) are new to the business environment as it focused on the real estate portfolio of the business. In the debate of Corporate Real Estate, it is noted that the CRE is undermanaged resources of the organization. It is noted that a substantial percentage of real estate is held by the organization over other assets of the total asset structure. The hotel industry confirms around 58 percent of the holding of the real estate portfolio over the total assets. Thus, the strategic use of CRE is imperative for the performance of the hotel as well as the Sustainable Competitive Advantage (SCA). With this intention, the study designed to identify possible CRE strategies and their impact on the performance of the hotel industry in Sri Lanka. Thus, the objectives of the study defined as to examine CRE strategies for the hotel industry in Sri Lanka; to examine indicators of performance of the hotel industry in Sri Lanka; to analyse relationship between of CRE strategies and performance of hotel in Sri Lanka; and finally, to analyse mediator impact of SCA on CRE strategies and Performance of hotels in Sri Lanka. Resource Base View (RBV) was used to conceptualize the relationship between CRE and the Performance as well as the mediator impact of Sustainable Competitive Advantage between CRE and Performance of the hotel. The study used literature review and the expert review supported by Analytic Hierarchical Approach with Lawshe's content validity ratio to investigate CRE strategies and its indicators.